Assessing Access-to-Justice Outreach Strategies - Prescott, J. J. (2018)
The need for prospective beneficiaries to “take up” new programs is a common stumbling block for otherwise well-designed legal and policy innovations. I examine the take-up problem in the context of publicly provided court services and test the effectiveness of various outreach strategies that announce a newly available online court access platform. I study individuals with minor arrest warrants whose distrust of courts may dampen any take-up response. I partnered with a court to quasi-randomly assign outreach approaches to a cohort of individuals and find that outreach improves take-up, that the type of outreach matters, and that online platform access is itself effective